2021
DOI: 10.3390/jcm10061263
|View full text |Cite
|
Sign up to set email alerts
|

Level of Adiponectin, Leptin and Selected Matrix Metalloproteinases in Female Overweight Patients with Primary Gonarthrosis

Abstract: The aim of this study was to assess levels of adiponectin (ACRP-30) and leptin in serum and synovial fluid (SF) of overweight females with primary gonarthrosis (GOA) and to look for their correlations with clinical status and the level of biochemical OA biomarkers: matrix metalloproteinase (MMP) 1, MMP-9 and tissue inhibitor of metalloproteinase (TIMP-1). The studied group consisted of 39 overweight females undergoing primary total knee arthroplasty as a result of GOA. The stage of GOA was evaluated according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…5,6,8,9 e present study investigated the relationship between e ndings of this study are consistent with the previous studies. [7][8][9][10][11] In the third round of the National Health and Nutrition Examination Survey (NHANES) study , metabolic syndrome was more prevalent in people with gonarthrosis. 11 In the Michigan Bone Metabolism and…”
Section: Resultsmentioning
confidence: 99%
“…5,6,8,9 e present study investigated the relationship between e ndings of this study are consistent with the previous studies. [7][8][9][10][11] In the third round of the National Health and Nutrition Examination Survey (NHANES) study , metabolic syndrome was more prevalent in people with gonarthrosis. 11 In the Michigan Bone Metabolism and…”
Section: Resultsmentioning
confidence: 99%
“…It is indispensable to explore the key factor leading to enhanced fatty acid oxidation in RA milieu. Leptin has been considered a link between the neuroendocrine and immune systems [32,33], which exhibits proinflammatory and pro-catabolic actions on cartilage [34][35][36]. However, Wang et al showed that leptin-JAK/STAT3 promoted breast cancer stemness and chemoresistance via upregulating lipid metabolism through FAO [19], providing new light to better understanding of the role of lipid metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…At the early OA stages, the Hoffa fat pad (IPFP—infrapatellar fat pad) increases its activity. The exact mechanism of the development of these changes in early OA is not clear but may consist in increased production of cytokines, adipokines, interleukins, and growth factors secreted by IPFP, which accelerate cartilage destruction through enhanced production of matrix metalloproteinases [ 1 , 61 , 62 ]. There are also no data showing changes in the IPFP volume in early OA.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is one of the most prevalent inflammatory diseases of the osteoarticular system and one of the leading causes of disability worldwide, affecting approximately 250 million people [ 1 , 2 , 3 ]. It causes joint pain, limits physical and social activity, and often leads to chronic disability [ 2 ].…”
Section: Introductionmentioning
confidence: 99%